Implementation of Occupational Safety and Health (K3) for Increasing Employee Productivity - Ahmad Firman (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aimed to examine and analyze the effect of implementing occupational safety and health programs on employee productivity at PT. Pertamina (Persero) Regional VII Sulawesi. The population used in this study are employees who work at PT. Pertamina (Persero) Makassar BBM Terminal with a total of 160 employees. The determination of the number of samples was obtained using the Slovin formula so that the number of samples used in this study was 62 employees. The source of data used in this research is primary data. Primary data from this study were obtained from questionnaires filled in by employees at PT. Pertamina. Data analysis used a validity test, reliability test, multiple linear regression analysis, partial test, simultaneous test, and determination test. The results showed that occupational safety and occupational health positively influence employee productivity variables at PT. Pertamina (Persero) Makassar Fuel Terminal. Meanwhile, the work safety program variable has the dominant influence on employee productivity.